The place of mathematics in the training of indigenous teachers in the Alto Solimões Region/AM - Elisângela Aparecida Pereira de Melo; Gerson Riberiro Bacury; Pedro Ferreira da Silva; Domingos Anselmo Moura da Silva (Arizona State University, 2020)
This article approaches the mathematical practices in the Degree Course in Indigenous Teacher Training of the Federal University of Amazonas/Campus of Benjamin Constant, in a context of cultural and linguistic diversity. For reflection on this theme, we take as a starting point the following question: In what formative terms the mathematical practices, through Concrete Material, have repercussions in the ways of teaching and learning of the indigenous students of the group of Alto Solimões/UFAM? In this sense, we aim to describe the different methodological approaches to the teaching and learning of some concepts in the scope of Flat Geometry, together with the indigenous students of the Undergraduate Course in Training of Indigenous Teachers/UFAM. The study has a qualitative approach based on ethnographic research, with the collection and analysis of information: impressions, perceptions and episodes with employees, as well as interdisciplinary, intracultural and intercultural activities enhanced in the understanding of some concepts of Flat Geometry, with emphasis on the baskets of the Ticuna artisans. Our reflections show, among other things, the acquisition of new knowledge, the creation, elaboration and proposition of different activities and mathematical practices for the future teaching actions in the schools of their communities.